الإفصاح عن الاستثمار في الموارد البشرية في التقارير المالية للوحدات الاقتصادية العراقية - الغبان ثائر صبري; ياسين سناء احمد (Journal of Economics and Administrative Sciences, 2007)
Abstract The economic entities view about human resources has been changed from traditional view based on the resources as one of production factors required for achieving the activities that lead to create products in turn for financial substitute embodied in wages, toward contemporary view consider human resources the most important richest investments, a real source for continuing, developing, and achieving competitive advantage for the entity. From that point, this research dealt with studying the subject of disclosing investment information of human resources in the financial reports of Iraqi economic entities. The research ended with stating a suggestive model for the analytical statements enclosed with financial reports to disclose investment information of human resources for handling the research problem. This problem representing in that the financial reports prepared by Iraqi economic entities lack accounting disclosure of investment information of human resources. This problem made these reports reveal that the available economic entities resources are only financial regardless of their importance and roles in exploiting financial resources in the best way that achieve the entity competitive advantage.